PROBLEMATIKA PEMBELAJARAN DARING MAHASISWA JURUSAN MANAJEMEN PENDIDIKAN ISLAM PADA MASA PANDEMI COVID-19 - Nurfadilah, Nurfadilah; Kasmawati, Kasmawati; Mardhiah, Mardhiah (Educational Leadership: Jurnal Manajemen Pendidikan, 2022)
Abstrack: Problems of Online Learning Students Departement of Management Islamic Education During the Covid-19 PandemicThe research that aims to describe the problems of online learning for students majoring in Islamic Education Management class 2017 Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar during the covid-19 pandemic. By using the management method of student management. The results of this study indicate that the problems of online learning are experienced by both lecturers and students. The competence factor of educators/lecturers is that lecturers are required to study IT further so that in preparing the material to be taught it can be maximized. Limitations of lecturers in controlling the ongoing online learning. Limited quota needed to access the internet network in online learning. Inadequate network access, a number of students live in areas that do not have internet access, such as in remote villages and geographically located areas that do not allow for a stable internet network. Solutions in overcoming problems create a conducive learning atmosphere to improve student understanding, provide training to lecturers to improve lecturers' abilities in using IT, expand network access for learning resources so that they can run effectively and efficiently, and the government distributes/provides free quota assistance for students. Abstrak: Problematika Pembelajaran Daring Mahasiswa Jurusan Manajemen Pendidikan Islam pada Masa Pandemi Covid-19Penelitian ini bertujuan untuk mendeskripsikan problematika pembelajaran daring pada mahasiswa jurusan Manajemen Pendidikan Islam angkatan 2017 Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar pada masa pandemi covid-19. Dengan menggunakan  metode  manajemen pengelolaan peserta didik. Hasil penelitian ini menunjukkan bahwa problematika pembelajaran daring dialami oleh dosen maupun mahasiswaFaktor kompetensi pendidik/dosen, dosen diharuskan untuk belajar IT lebih jauh sehingga dalam menyiapkan materi yang akan diajarkan dapat lebih mkasimal. Keterbatasan dosen dalam mengontrol berlangsungnya pembelajaran daring. Keterbatasan kuota yang dibutuhkan untuk mengakses jaringan internet dalam pembelajaran daring. Akses jaringan yang tidak memadai, sejumlah mahasiswa tinggal di wilayah yang tidak memiliki akses internet, seperti di pelosok desa dan wilayah dengan letak geografis yang tidak memungkinkan untuk jaringan internet yang stabil.  Solusi dalam mengatasi problematika tersebut, yaitu menciptakan suasana belajar yang kondusif untuk meningkatkan pemahaman mahasiswa, memberikan pelatihan-pelatihan kepada dosen untuk meningkatkan kemampuan dosen dalam penggunaaan IT, perluasan akses jaringan untuk sumber belajar agar dapat berjalan secara efektif dan efisien, dan pemerintah menyalurkan/memberikan bantuan kuota gratis bagi mahasiswa.